Awareness of Climate Change and Climate Change Adaptation Strategies Among Secondary School Students in Ogbaru Local Government Area of Anambra State, Nigeria - Oguejiofor, Chidumebi Ngozi; Okafor, Patrick Chinenye; Ani, Anthonia Nwabugo; Nwogbo, Mercy Obianuju; Chukwu, Pius Okechukwu (European Scientific Journal, ESJ, 2025)
This study investigated the awareness of climate change and climate change adaptation strategies among secondary school students in Ogbaru Local Government Area of Anambra State, Nigeria. Two research questions guided the study, and two null hypotheses were formulated for the study and tested at a 0.05 level of significance. The study employed a descriptive survey research design. The population of the study consisted of 8,564 JSS and SS students (4,720 JSS and 3,844 SS) from the 9 public secondary schools in the area. The sample size consisted of 170 students (94 JSS and 76 SS students) from the four schools sampled for the study using a simple random sampling technique (balloting). Data was collected using the 40-item climate change awareness and adaptation strategies questionnaire (CCASSQ) developed by the researchers and validated by experts. An estimate of the stability of the instrument yielded a reliability coefficient of 0.88 using Cronbach’s Alpha statistic. Mean and Standard Deviation were used as descriptive statistics to answer the research questions while independent samples t-test was adopted as inferential statistic. The findings revealed high level of awareness of climate change by the JSS and SS students. It also indicated high level of awareness of climate change adaptation strategies by JSS and SS students in Ogbaru LGA of Anambra State. Based on the findings, it was recommended that the government should start working on the schools by providing infrastructural facilities like wind vans and rain gauges that could enable the teachers to meet the demands of this era of climate change.